2013
DOI: 10.1161/hypertensionaha.113.01514
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Interleukin-17 Soluble Receptor C Suppresses T H 17 Cells, Oxidative Stress, and Hypertension in Response to Placental Ischemia During Pregnancy

Abstract: Pre-eclampsia (PE), new onset hypertension with proteinuria during pregnancy, is associated with chronic inflammation and placental oxidative stress (ROS). Chronic IL-17 increases blood pressure (MAP), autoantibodies (AT1-AA) and ROS during pregnancy. The objective of this study was to determine if TH17 suppression via IL-17RC (recombinant receptor C) decreases pathophysiology associated with placental ischemia (RUPP). On gestation day 14, mini-osmotic pumps infusing 100 pg/day of IL-17RC were implanted into p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 23 publications
(27 reference statements)
2
93
0
Order By: Relevance
“…35 We have previously reported that circulating CD4þIL-17Aþ lymphocytes are increased in the circulation and kidneys of HELLP rats, but not in the spleen, placenta, or liver indicating that the source of IL-17 does not come just from TH17 lymphocytes, which were not found to be significantly increased in rats with HELLP syndrome. 21 We have also previously reported that administration of IL-17 to pregnant rats increases MAP and CD4þ lymphocytes [36][37][38] Figure 3. The ET A blockade attenuates hypertension in HELLP rats.…”
Section: Discussionmentioning
confidence: 83%
“…35 We have previously reported that circulating CD4þIL-17Aþ lymphocytes are increased in the circulation and kidneys of HELLP rats, but not in the spleen, placenta, or liver indicating that the source of IL-17 does not come just from TH17 lymphocytes, which were not found to be significantly increased in rats with HELLP syndrome. 21 We have also previously reported that administration of IL-17 to pregnant rats increases MAP and CD4þ lymphocytes [36][37][38] Figure 3. The ET A blockade attenuates hypertension in HELLP rats.…”
Section: Discussionmentioning
confidence: 83%
“…PE is thought to be a multifactorial disease that involves oxidative stress, endothelial dysfunction, inflammation, and immunity [3][4][5]. Previous studies of PE have shown interactions between inflammation and endothelial dysfunction [6] and between inflammation and oxidative stress [7]. We also previously found a relationship between oxidative stress and immunity in placental trophoblasts in PE [8].…”
Section: Introductionmentioning
confidence: 86%
“…For example, T cells from angiotensin II-infused mice produce and release more IL-17, and IL-17 knockout mice are protected from angiotensin II-induced hypertension [18]. In addition, data from the LaMarca laboratory indicate that infusion of IL-17 into normal pregnant rats leads to chronic increases in blood pressure [19] and that blocking IL-17 activity with the soluble receptor to the cytokine prevents pregnancy-induced increases in blood pressure [20]. Although the mechanisms for IL-17-induced hypertension remain unclear, there is some evidence suggesting that IL-17 promotes hypertension by reducing endothelial nitric oxide synthase [21].…”
Section: Immune System Activation and Hypertension: A Brief Overviewmentioning
confidence: 99%